Assessing the suitability of stress tolerant early-maturing maize (Zea mays) inbred lines for hybrid development using combining ability effects and DArTseq markers - Adewale, Samuel A.; Badu-Apraku, B.; Akinwale, R.O. (Wiley, 2023)
Identification of hybrids for commercialization is crucial for sustainable maize production in sub-Saharan Africa (SSA). One hundred and ninety test crosses, 10 tester × tester crosses + 10 hybrid checks were evaluated across 11 environments, 2017 to 2019. Inheritance of grain yield under Striga infestation, optimal and across environments was influenced by additive genetic action, but there was greater influence of nonadditive gene action under drought stress conditions. Nine, seven and two inbreds had significant and positive general combining ability (GCA) effects for grain yield under Striga-infested, optimal and drought stress environments, respectively, and would contribute high grain yield to their progenies. Heterotic grouping methods based on specific and GCA, GCA effects of multiple traits and DArTseq markers classified the inbreds into five, three and two heterotic groups, respectively, across research conditions. The DArTseq markers method that classified the inbred lines into two major heterotic groups and was one of the most efficient methods should be adopted for practical purposes in maize breeding programmes in SSA. Hybrids TZEI 7 × TZdEI 352, TZEI 1238 × TZEI 7 and TZEI 1252 × TZEI 7 had outstanding grain yield under contrasting environments and should be tested on-farm for commercialization in SSA.